Moral distress, attitude toward death, and palliative care core competencies among ICU nurses: a cross-sectional study - Mengyun Peng; Qin Guan; Xiaoling Zhu (BMC Palliative Care)
Abstract Background Palliative care is becoming more widely acknowledged as a crucial part of intensive care for all patients with life-threatening illnesses. Intensive care unit (ICU) nurses regard as a lead role to facilitate this integration, which require nurses to possess professional and comprehensive core competencies. However, there is little knowledge about the palliative care core competencies among ICU nurses. Aims To explore the association of moral distress, attitude toward death, and palliative care core competencies of ICU nurses, and explore the mediating role of attitude toward death. Methods This is a quantitative, cross-sectional study. Random cluster sampling method was used. 342 ICU nurses were selected from 5 hospitals across 4 provinces in China. Participants were evaluated using the Moral Distress Scale-revised (MDS-R), the Attitude toward Death Profile-Revised (DAP-R), and the Palliative Care Nurses’ Core Competencies Scale (PCNCC). This study followed the STROBE statement. Results The level of palliative care core competencies among ICU nurses is moderate. Moral distress and negative attitude toward death are negatively associated while positive attitude toward death is positively associated with core competencies in palliative care among ICU nurses. Attitude toward death partially mediates the relationship between moral distress and core competencies. Conclusion Link between moral distress, attitude toward death, and palliative care core competencies among ICU nurses was found in this study.